The death of Christian Britain: understanding secularisation ; 1800 - 2000 - Brown, Callum G. (Christianity and society in the modern world, 2009)
This text challenges the generally held view that secularisation has been a long and gradual process beginning with the Industrial Revolution, and instead proposes that it has been a catastrophic short-term phenomenon starting with the 1960s